Influencing Factors of Intrinsic Structure and Sodium Storage Properties of Carbonized Petroleum Coke - Jingwen QU; Haile CAI; Yongyi SONG; Shudong ZHANG; Dong YAN; Rui MA (Liaoning Shiyou Huagong Daxue xuebao, 2025)
The anode materials play a crucial role in the components of sodium⁃ion batteries. Petroleum coke serves as an important precursor for the preparation of carbon anode for sodium⁃ion batteries. In this study, the effects of carbonization temperature and sulfur content on the structure of petroleum coke anode were characterized by XRD and Raman spectroscopy, and the changes of sodium storage properties for different structured anodes were analyzed. The results show that the anode has a balanced defect density and interlayer spacing and excellent conductivity, which exhibits better electrochemical performance at 1 000 ℃. The discharge capacity at a current density of 50 mA/g is 434 mA•h/g. The presence of sulfur inhibits the rearrangement and growth of carbon layer. With the increase of sulfur content of petroleum coke, the anode material exhibits higher sodium storage capacity and better cycle life and rate performance, while the initial coulomb efficiency decreases from 65% to 54%, posing significant challenges for future research.